Efficacy of azithromycin 1.5% eye drops in childhood ocular rosacea with phlyctenular blepharokeratoconjunctivitis - Doan, Serge (Springer, 2013)
BACKGROUND: The purpose of this study is to report the efficacy of azithromycin 1.5% eye drops in children with ocular rosacea and phlyctenular blepharokeratoconjunctivitis. This retrospective study from January 2009 to March 2010 included 16 children treated with lid hygiene plus azithromycin 1.5% eye drops (Azyter®): 3-day treatments (1 drop twice a day) every 10 days, reduced based on efficacy to one treatment every 15 days and then to one treatment per month. RESULTS: Nineteen eyes of six boys and ten girls, aged 4 to 16 years (mean, 9.3 ± 4.0) were included. The disease was previously resistant to lid hygiene (all the patients), oral erythromycin (one patient), and intermittent topical steroids (six patients). The median duration of each phase of azithromycin treatment (i.e., three, two, and one treatments per month) was 2 months. Ocular inflammation was controlled by azithromycin alone in 15 patients. In one uncontrolled case, cyclosporine 2% eye drops was added at month 5. Bulbar conjunctival hyperemia resolved completely within 1 month in all eyes, whereas conjunctival phlyctenules and corneal inflammation took longer to improve, with a complete resolution within 3 to 10 months. Blepharitis grade decreased from 2.31 ± 0.79 to 1.50 ± 0.73. Treatment was stopped after a median of 6 months (from 4 to 10 months) without recurrence of corneoconjunctival inflammation (median follow-up without treatment, 11 months). Six cases of ocular irritation were reported, two of which led to treatment withdrawal. CONCLUSION: Azithromycin 1.5% eye drops is an effective treatment for phlyctenular keratoconjunctivitis complicating childhood ocular rosacea.